Cerebellum and temporal lobes of Alzheimer's disease patients present with an altered glycobiological state. (1st February 2022) - Carre, Ivo A; Solomon, Shiden; Mondal, Mrityunjoy; Sampathkumar, Nirmal Kumar; Troakes, Claire; Mitchell, Jacqueline
Abstract: Background: A major challenge facing Alzheimer's Disease (AD) research is the slowing or prevention of synaptic pruning, a pathology associated with driving the progression of AD's clinical symptoms. Currently, the mechanism by which pruning occurs is not well understood and whilst the complement cascade has been implicated (Hong et al., 2016), there are still questions regarding cellular targets and regulation. Therefore, exploration of additional regulatory factors is likely to offer novel targets for future therapeutic strategies. One key regulatory factor we propose is glycosylation, specifically the role of sialic acid 'caps'. Here, we show that glycobiological status of individual brain regions appears to be tied to AD pathology, suggesting an exciting avenue for novel therapeutic approaches. Method: Temporal lobe and cerebellar tissue samples from AD (n=20) and age matched control (n=20) brains were homogenised in RIPA lysis buffer supplemented with phosphatase and protease inhibitors and assessed for Neuraminidase 2‐4 and sialic acid levels. Neuraminidase levels were assessed using western blot whilst total, bound and free sialic acid levels were assessed using a fluorometric assay. Result: Significant increases in free sialic acid were observed in the temporal lobes of AD patients compared to controls, with no significant differences detected in total and bound sialic acid. Conversely, both total and bound sialic acid were significantly increased in the cerebellum, while levels of free sialic acid were unchanged. Moreover, reductions in Neu 2 and Neu 4 were observed in the temporal region during AD, with no significant changes in the cerebellum. Conclusion: These findings show that mild increases in free sialic acid are associated with AD pathology in vulnerable brain regions such as the temporal lobe. Crucially, they show significant increases in total and bound sialic acid in the cerebellum, a region minimally impacted by AD pathology (Larner, 1997). This suggests there are key differences between cerebellar and temporal lobe sialylation in AD, that may in turn underpin the differential vulnerability of these brain regions to disease linked degenerative processes. Understanding more about the mechanisms that drive this sialylation may prove valuable in the quest for novel therapeutic targets for AD.